Lumped-element model of plasmonic solar cells. (September 2018) - Kim, Chang-Hyun; Seitanidou, Maria; Jin, Jong Woo; Bonnassieux, Yvan; Horowitz, Gilles; Vangelidis, Ioannis; Lidorikis, Elefterios; Laskarakis, Argiris; Logothetidis, Stergios
Highlights: A simple and versatile electrical model for plasmonic solar cells is proposed. The model precisely describes the behavior of organic/nanoparticle devices. Predictive simulation suggests a strategy for efficient power conversion. Abstract: Although metallic nanostructures in solar cells provide versatility in designing useful plasmonic architectures, understanding is still limited on how to exploit their multi-scale contribution as tunable performance. In this article, we suggest a characteristic model that develops into a simple and robust tool for guiding optimization of plasmonic solar devices. The model is conceptually based on the breakdown of the active region into intrinsic and plasmonic sub-circuits, by which the terminal currents are directly correlated with particle geometries and local improvement. Measurements from organic cells support the validity of our theory, and a series of simulation provides further insights into the critical trade-off between voltage and current generation, finally offering a strategy for efficiency enhancement.